THE PORTRAYAL OF GENDER AND RACE IN CARS TRILOGY - Rahayu, Nurhadianty (ATAVISME, 2019)
As the most commercially successful animated film, Cars trilogy, produced by Pixar Animation Studios, are opted to be analysed due to its impact on formulating perception of gender and race. Considering that intolerance and gender-based injustice still happens within our society, any discussion about gender and race portrayal, particularly through films, becomes urgent. The study aims at investigating how gender and race are portrayed in Cars trilogy. Gender portrayal is analysed through Beauvoir?s concept of immanence and transcendence and Finklea?s themes about masculinities. The portrayal of race is investigated using McLaren?s critical multiculturalism. The study uses the descriptive analytical interpretative method. The data analyzed are the characters, dialogue, and plot. The result shows that men and women are portrayed as equal but the stereotypes are still visible. Men are portrayed not only brave but also confident. Males? romantic interest is manifested in heterosexual desire and male bosses are driven by profit. Women can be successful in racing if she dares to intervene the bureaucracy or is given opportunity by men. Different accent of English is seen as less capable and white characters are not always portrayed unproblematic.